Folklore in the Development of Tourism Based on Story Telling of Karo Culture in Dokan Village - Sinulingga, Jekmen; Tampubolon, Flansius (Budapest International Research and Critics University, 2021)
This article entitled “Folklore of Karo in the Development of Storytelling-Based Cultural Tourism in Dokan Village” was researched by Folklore approach. This study formulates 2 problem formulations, namely the form of an inventory of Karo folklore and cultural values for the development of cultural tourism in Dokan Village, and the role of Karo Folklore in the development of cultural tourism in Dokan Village, which is beneficial for the development of cultural tourism in the Karo area. The method used in this study is qualitative paradigm of ethnographic model developed by spreadly applies 12 steps of observation and 12 steps of interview. The findings this study are expected to be benefit Karo community as a culture owners, researchers, and students who want to explore the folklore of Karo community and the development of cultural tourism in Dokan Village.